Constructing multi-theory vignettes to measure the application of knowledge in ambivalent educational situations - Lohse-Bossenz, Hendrik; Bloss, Christopher; Dörfler, Tobias (Frontiers in Education, 2022)
Research on evidence-based argumentation shows that (pre-service) teachers have difficulties in orienting their actions to existing theories and empirical evidence. This article addresses the knowledge content needed for this and presents a vignette-based procedure. Within each vignette, two different theoretical perspectives are addressed. The behaviour of a teacher can be either suitable or unsuitable from both perspectives or more or less suitable depending on the perspective. In study 1, the procedure is piloted and in study 2, an intervention on a specific area of knowledge takes place. The results show that participants differentiate the vignettes as expected. The intervention leads to corresponding increases in knowledge, which likely relates to a change in the evaluations. The presented approach is discussed with regard to possible applications in the context of research on evidence-based argumentation.